Pendidikan Literasi Media untuk Menghadapi Risiko Online dan Jaringan Komunikasi Remaja di Internet - Amia Lufhfia (Universitas Al Azhar Indonesia, 2015)
Internet usage can not be separated from the adolescents’ life nowadays. They use internet mainly for obtaining pleasure, although some of them are using it to help them in doing their school assignments. Internet is like a double edged sword for adolescents. In ternet has risks too for the adolescents, such as exposure to pornography, violent / racism content, misleading advertising, cyber bullying, and to certain extent we also heard that the contact with pedophile was done through internet (social media). Internet has made the outsider can reach adolescents from their personal subsystems. Internet is able to take them out of the boundaries of the community level and out of the social network which has been “kept” them. The question is, “are they aware the risk of using the internet?” To prevent things get worse in adolescents’ abuses, media literacy education is the answer and should be part of the Indonesian education system.